MIGRATION OF THE INTRAUTERINE CONTRACEPTIVE INTO THE BLADDER WITH THE FORMATION OF A SECONDARY STONE AND VAGINAL-VESICAL FISTULA - Владимир Вячеславович Павленко; Евгения Александровна Каменева; Ольга Владимировна Кулева; Татьяна Ивановна Петришина (Медицина в Кузбассе)
The paper presents a case of migration of an intrauterine contraceptive into the bladder cavity with the subsequent formation of a vaginal-vesical fistula and a secondary stone on an intrauterine contraceptive. The intrauterine contraceptive was removed by excision with a hook electron and traction for a foreign body without technical difficulties. The bladder was drained and the vaginal-vesicular fistula closed on its own.